Mass spectrometric identification of mycobacterium tuberculosis antigens in bronchoalveolar lavage fluid at the end of curative TB treatment. - Tenkeu, Sylvain Zemsi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.